Utilization of Brackish Water as a Potable Water Source through Reverse Osmosis Technology: A Case Study in Taddutan Island, Saliki Village, Kutai Kartanegara - Ansahar; Ryan Irawan; Aldi Muhammad Miftahuddin; Aura Nazwa; Regita; Zefanya Hosiana Cindy Prastica (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2026)
Brackish water, although often neglected due to its high salinity, represents a strategic water source for coastal communities facing freshwater scarcity. This study addresses a research gap in the utilization of heavily contaminated brackish water in tropical peatland areas of East Kalimantan through an integrated hybrid technology approach that combines local governance and renewable energy. Water samples were collected from two locations in Taddutan Island (RT 7 and RT 8) in December 2023 and analyzed at the accredited DLHK Kutai Kartanegara Environmental Laboratory. Results showed that raw water exhibited salinity of 0.22–4.42‰, total dissolved solids (TDS) of 244.6–4,658.5 mg/L, chemical oxygen demand (COD) of 18.4–46.4 mg/L, and extreme microbiological contamination (Total Coliform reaching 87,320 MPN/100 mL). The local PAMSIMAS unit failed to completely eliminate Total Coliform despite significantly reducing TDS. Based on these findings, a four-stage hybrid treatment system was designed: (1) coagulation-flocculation (alum + KOH), (2) multistage filtration (rapid sand, manganese zeolite, activated carbon), (3) reverse osmosis (RO) using brackish water membrane, and (4) UV disinfection. The system is operated using a 2,500-watt solar photovoltaic system (PLTS) to ensure energy sustainability, while governance by the Village-Owned Enterprise (BUMDes) Mekar Sejati and community Willingness to Pay (WTP) (IDR 50,000–150,000/month) guarantees operational sustainability. The novelty of this research lies in the integration of three pillars: (i) RO hybrid technology with adaptive pretreatment for peatland brackish water, (ii) integration of PLTS as a renewable energy source, and (iii) BUMDes-based governance. This model has high replication potential across hundreds of coastal peatland villages in Indonesia facing similar challenges